(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2024)
Elio Vittorini’s Le città del mondo is a work-in-progress, a magma of ideas and projects conceived, then altered, abandoned, and resumed in new forms; the printed edition is a posthumous edition, constructed according to non-philological criteria. In this situation, it is more important than ever to focus on what the author himself published during his lifetime. From the project Le città del mondo, two publications were issued during the author’s lifetime, covering the same portion of the text: one in France, published by Gallimard, and the other in England, by Jonathan Cape. In 1997, Edoardo Esposito compared these with the first edition, identifying some textual discrepancies; however, the issue has remained underexplored, and no material evidence seemed to support the authorship of the Cape and Gallimard operations. Two documents have been found in the Vittorini Archive at the Centro Apice, filed among the preparatory materials for magazine extracts, which share the same characteristics as the foreign editions identified by Esposito. Through a series of collations and comparisons, the probable authorship of the editorial operation has been verified, allowing for reflection on its purposes.